ADULT LEARNING BASICS - Rothwell, William J., 1951- (Association FOR TALENT DEVELOPMENT, 2020)
Everything you need to know to get started as an adult learning professional. Instructing adults is dramatically different from teaching children, and the effectiveness of training programs is often dictated by how well they apply the principles of adult learning. Enhance your programs with the latest research into how adults learn, remember, and apply knowledge and skills. Adult Learning Basics examines the principles of adult learning theory and how they relate to the training function by addressing individual learning competencies, organizational learning climate, and technology-related issues. This new edition features the latest research on generational trends, microlearning, and other TD breakthroughs. Exercises at the end of each chapter help you apply the science and theory to your real talent development challenges. Elevate your practice with this thorough guide, and keep it as an indispensable resource.